We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
152
3
avatar+893 

Answer: 256/17

 Mar 16, 2019
 #1
avatar+893 
+1

I tried setting the side length to a. Then, I used the length given and got an equation for the third small triangle. Then I got confused on how to solve that. Is there any other way?

 Mar 16, 2019
 #2
avatar+103917 
0

Call the side of the square, S

 

So...the area of the square = S^2

 

The area of the small triangle at the bottom left  = S* [ sqrt (4^2 - S^2) ] /2 / 2      (1)

 

The area of the small triangle at the top right = S* [ sqrt (5^2 - S^2)] /2        (2)

 

And the area of the small triangle at the top left =   [ S  - sqrt (4^2 - S^2)] [ S - sqrt (5^ - S^2) ] / 2     (3)

 

And the area of the right triangle = 6     (4)

 

So

 

(1) + (2) + (3) + (4)  =  S^2

 

S* [ sqrt (16 - S^2 ] /2  + S* [ sqrt (25 - S^2)] / 2   + [ S  - sqrt (16 - S^2)] [ S - sqrt (25 - S^2) ] / 2 + 6 = S^2 

 

 

S* [ sqrt (16 - S^2 ]   + S* [ sqrt (25 - S^2)] + [ S  - sqrt (16 - S^2)] [ S - sqrt (25 - S^2) ]  + 12 = 2 S^2 

 

 

S* [ sqrt (16 - S^2 ]   + S* [ sqrt (25 - S^2)] + [ S  - sqrt (16 - S^2)] [ S - sqrt (25 - S^2) ]  + 12 = 2 S^2 

 

S* [ sqrt ( 16 - S^2) ] + S*[ sqrt (25 - S^2) ]  + S^2  - S*[ sqrt (16 - S^2)] - S* [ sqrt (25 - S^2)] +

sqrt [ ( 16 - S^2)  (25 - S^2) ] + 12  = 2S^2

 

 

sqrt [ (16 - S^2) (25 - S^2)] =  S^2 - 12       square both sides

 

(16 - S^2) ( 25 - S^2)  =  S^4 - 24S^2 + 144

 

400 - 41S^2 + S^4  = S^4 - 24S^2 + 144

 

17S^2  - 256  = 0

 

17S^2 = 256

 

S^2  =   256 / 17

 

 

cool cool cool

 Mar 16, 2019
 #3
avatar+893 
0

Thanks!!!

dgfgrafgdfge111  Mar 18, 2019

34 Online Users

avatar